Relationship Between Motor Capacity of the Contralesional and Ipsilesional Hand Depends on the Side of Stroke in Chronic Stroke Survivors With Mild-to-Moderate Impairment - Varghese, Rini; Winstein, Carolee J. (Frontiers in Neurology, 2020)
There is growing evidence that after a stroke, sensorimotor deficits in the ipsilesional hand are related to the degree of impairment in the contralesional upper extremity. Here, we asked if the relationship between the motor capacities of the two hands differs based on the side of stroke. Forty-two pre-morbidly right-handed chronic stroke survivors (left hemisphere damage, LHD = 21) with mild-to-moderate paresis performed distal items of the Wolf Motor Function Test (dWMFT). We found that compared to right hemisphere damage (RHD), the relationship between contralesional arm impairment (Upper Extremity Fugl- Meyer, UEFM) and ipsilesional hand motor capacity was stronger for LHD (R^2_LHD = 0.42; R^2_RHD < 0.01; z = 2.12; p= 0.03) and the slope was steeper for LHD (t = -2.03; p= 0.04). Similarly, the relationship between contralesional dWMFT and ipsilesional hand motor capacity was stronger for LHD (R^2_LHD = 0.65; R^2_RHD = 0.09; z = 2.45; p= 0.01) and the slope was steeper for LHD (t = 2.03; p= 0.04) compared to RHD. Multiple regression analysis confirmed the presence of an interaction between contralesional UEFM and side of stroke (β3 = 0.66 ± 0.30; p= 0.024) and between contralesional dWMFT and side of stroke (β3 = -0.51 ± 0.34; p= 0.05). Our findings suggest that the relationship between contra- and ipsi-lesional motor capacity depends on the side of stroke in chronic stroke survivors with mild-to-moderate impairment. When contralesional impairment is more severe, the ipsilesional hand is correspondingly slower in those with LHD compared to those with RHD.